ANALISIS PENGARUH HUMAN CAPITAL, ANGKATAN KERJA, DAN BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI PROVINSI SUMATERA BARAT, 2007-2011 - , TARULI DAMERIA. S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to analyze the influence of human capital (community literacy rate, average length of schooling), labor force and capital expenditure district/ city to the economic growth of West Sumatra Province 2007-2011. The data used in this study is a secondary data obtained from the BPS West Sumatra and Central Bureau of Statistics. The variables used in this study is the gross domestic product regional constant prices of 2000, literacy rates, average length of school level, labor force participation rate, and the proportion of capital expenditures of government expenditure district /city of West Sumatra Province. The analytical tool used in this study is a panel data regression. The results showed that, the literacy rate and the average length of school a positive effect on economic growth in the province of West Sumatra 5 percent confidence level. Labor force and capital spending growth is not the province of West Sumatra. This study is expected to be the input for the government of West Sumatra, especially related to policy-making in order to increase economic growth. Keywords: Economic growth, human capital, labor force, government expenditure